Paradiplomasi melalui Kerja Sama Sister City; Analisis Peran UCLG ASPAC pada Kemitraan Jakarta-Kuala Lumpur - Saskia Salsabilla; Zharifah Putri; Nandra Rasya Naysilla; Anandyo Putra Wirawan; Laila Syakira; Joshua Alexander Aritha Pumala Bangun; Bilqis Oktaviani Putri (Universitas Nahdlatul Ulama Blitar, 2026)
This study aims to analyze the role of the United Cities and Local Governments Asia-Pacific (UCLG ASPAC) as a facilitator in intercity cooperation between Jakarta and Kuala Lumpur. This collaboration has evolved in line with the increasing needs of local governments to address various urban challenges, such as climate change, flooding, urbanization, and sustainable development. The study employed a descriptive qualitative method, with data collection techniques including interviews and documentation studies. Primary data were obtained through interviews with UCLG ASPAC representatives, while secondary data came from official documents, organizational reports, scientific journals, and various other relevant sources. The results indicate that UCLG ASPAC acts as a facilitator by providing a space for dialogue, liaising between stakeholders, managing knowledge transfer, and mediating intercity network governance. The organization successfully utilized regional forums to bring together the governments of Jakarta and Kuala Lumpur, resulting in sister city cooperation focused on environmental issues, flood management, and sustainable development. The research findings also indicate that a network-based approach, or network governance, enables local governments to participate more actively in international relations. However, the implementation of this cooperation still faces challenges in the form of limited regional authority and differences in institutional capacity in each city.